The need for biomedical scientists to have the right skills - Lloyd Mcleggon-Watkinson, Victoria Chalker (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Biomedical scientists play a pivotal role in the care and management of patients that is rarely seen in the public eye; it is also a specialist area that is constantly evolving. The nature of this evolution requires that registered Biomedical Scientists continually work towards achieving a skillset suitable for a continually developing speciality. These skills may begin to be acquired early in education and firmly established into a career and beyond. The dynamic nature of the sector often requires the integration of innovative technology, methodology and evidence-based practice to be implemented which requires Biomedical Scientists to continuously work to obtain updated knowledge in an ever-changing environment. Lloyd Mcleggon-Watkinson, a Biomedical Science Apprentice at the University of Salford, spoke with Dr Victoria Chalker, the Deputy Chief Scientific Officer for NHS England, to get to know how healthcare science has evolved over time but also about the importance of Biomedical Scientists updating their skills and practices for a modern laboratory setting. The Editors would like to thank Professor Richard Birtles (The University of Salford) for connecting us with Dr Victoria Chalker. Additional thanks go to Kim Allen, Alex Wilson and the NHS Communications Team, David Wells (Chief Executive of the Institute of Biomedical Science) and Sue Jones (Executive Head of Education – Institute of Biomedical Science) for reviewing this article and providing their insights.
Keywords: Biomedical science